Классификация соосных конических каналов - Ульев, Леонид Михайлович (НТУ "ХПИ", 2005)
Different variants of the coaxial conic channels are considered in the paper. The classification of these channels is executed. This classification helps to select coordinate system for mathematical formulation of liquid flow problem in such channels
Keywords: ламинарные течения; гидродинамика; конфузорное течение; кольцевые конические каналы; гидромоторы; двигатели авиационные; машины червячные; машины литьевые; теплообмен